✔ 最佳答案
This base case holds since 4^3 < 3^4.
To show that the inductive step holds, we need to show that:
if (n + 1)^3 < 3^(n + 1) holds, n^3 < 3^n holds.
Note that:
3^(n + 1) = 3 * 3^n
> 3n^3, since 3^n > n^3 by the inductive hypothesis
> (n + 1)^3. (see below)
Then, since we have shown that 3^(n + 1) > (n + 1)^3 holds if 3^n > n^3 holds and that the base case holds, the proof is complete.
<== Proof of 3n^3 > (n + 1)^3: ==>
By binomial expansion, we have:
(n + 1)^3 = n^3 + 3n^2 + 3n + 1.
So:
3n^3 > (n + 1)^3 ==> 3n^3 > n^3 + 3n^2 + 3n + 1 ==> 2n^3 - 3n^2 - 3n - 1 > 0.
Since 2n^3 - 3n^2 - 3n - 1 = 0 has a real solution on (2, 3) (this is true since f(2) and f(3) have opposite signs) and this is the only positive real solution via Descartes' Rule of Signs, we see that 2n^3 - 3n^2 - 3n - 1 > 0 holds on the interval [4, infinity). Back-tracking from this inequality yields 3n^3 > (n + 1)^3, and so the proof is complete.
<== END PROOF ==>